"Can quantum dot in form of molecular ground be implied in IETS to measure the voltage effectively by sudden potential rise due to phonon assisted electron tunneling as Klein paradox?". (2021) - Sharma, Amitabh; Prasad Verma, Umesh
Abstract: Sudden break in the passage of electron beam things conducting barrier shall either enhance or decrease electron beam with provided effect on spectral band of unknown metal, j/?dv –V at d 2/ dv 2 plot gives characteristic of tunnel junction. At liquid helium temperature qv = hὐ implication for JV curve is observed at bias V where v denotes the frequency of molecular compounds present in the barrier, In case barrier emitting phonon interacts with the lattice of implied nano particles like Ga, As Ge Se coupled barrier in molecular state can be observed a specific band of Raman spectra and infra red thermally nactivated long wave spectra as IETS under Josephson effect. Single quantum dot in ultraclean carbonnanotube can be annexed with novel double quantum dot as result of klein paradox. At relatvistic QFT. In this context single spin1/2 can be confined with the hole emplacement and confinement as second double dot.